Collective bargaining under non-binding contracts - Sabien Dobbelaere; Roland Iwan Luttens (Institute for the Study of Labor (IZA), 2011)
We introduce collective bargaining in a static framework where the firm and its risk-neutral employees negotiate over wages in a non-binding contract setting. Our main result is the equivalence between the non-binding collective equilibrium wage-employment contract and the equilibrium contract under binding risk-neutral efficient bargaining. We also demonstrate that our non-cooperative equilibrium wages and profits coincide with the Owen values of the corresponding cooperative game with the coalitional structure that follows from unionization.
urn:nbn:de:101:1-201104113917
Keywords: C71; J51; L20; 330; collective bargaining; union; firm; bargaining power; non-binding contract; Lohnverhandlungen; Verhandlungsmacht; Kooperatives Spiel; Theorie